Implementasi Peranan Humas Di Rumah Sakit Umum Daerah Kelas D Bantargebang Tahun 2025 - Nawangwulan, Kurniati; Restyanti, Yuli; Nurhalizah, Ninda; Alam, Nur (Jurnal Sintesis: Penelitian Sains, Terapan dan Analisisnya, 2025)
According to Workforce and Facilities, the number of complaints received by NHS Digital in England increased between October 2015 and March 2017, with 39.6% in December 2016 and 9.55% in November 2015, the two years with the fewest complaints, respectively. Furthermore, the Swedish Patient Advisory Committee receives approximately 30,000 complaints per year, a 17% increase from four years earlier. The study found that Public Relations at Bantargebang Class D Regional General Hospital (RSUD) has performed its primary roles as expert prescriber, communication facilitator, problem-solving process facilitator, and communication technician. While the roles are in accordance with Standard Operating Procedures (SOPs), implementation has not been optimal due to limited human resources, infrastructure, and inter-unit coordination. Public Relations plays an active role in providing strategic advice, facilitating two-way communication, handling patient complaints, and managing communication media, although some activities are still carried out manually and have not been digitally integrated. In conclusion, the role of Public Relations at Class D Bantargebang Regional General Hospital has been running according to the theory of the role of public relations according to Cutlip et al. (2011), although improvements are still needed in the aspects of HR competency, utilization of communication technology, and strategic planning so that this role can be implemented optimally.